A Research Review on the Evolution of Urdu Fiction in West Bengal: مغربی بنگال میں اُردو افسانے کا ارتقاء (تاریخی اور تحقیقی جائزہ) - Gul, Dr. Waseem Abbas (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Bengal has also played a special role in the evolution of Urdu language like other regions. As the education of Fort William College flourished in Bengal, Urdu prose flourished. But this does not prove that Urdu prose also originated from the time of Fort William College. On the contrary, current research indicates that Urdu prose existed even before . From 1800 to 1828 the activities of Fort William College continued with vigor. In this short period, Urdu prose developed a lot and gained an important place in Urdu literature. Mir Aman, Haider Bakhsh Haidari, Mazhar Ali Khan Villa, Beni Narayan, Nihal Chandla Hori, Mirza Ali Lutf, Mir Bahadur Ali Hussaini and other writers lifted Urdu prose from the floor and enthroned it in Bengal. This is the reason why in the latter half of the nineteenth century the Urdu language was able to express the modern trends, contemporary demands and problems of life with simplicity and ease, but unfortunately Lord Welsh and Sir John Gilchrist were disaffected and disturbed by the company. Had to resign. After these people left, the golden age of the college ended. If these people had stayed here for some time, the development and popularity of Urdu prose would have increased further. However, after the closure of the college on the order of Lord Dalhousie in 1854, the development of prose literature of Bengal was affected to a great extent, but what happened was that the Fort William movement gave Bengal the first place in the history of Urdu prose. In this connection, it is also worth mentioning that the first Urdu newspaper 'Jam Jahan Nama' was published from Bengal in 1822 under the editorship of Harihardt. Camps were first established here. Science and arts books were authored, compiled and translated. The work of printing and publishing also started in relation to dictionary, rules, history, geography, science and medicine and thus the prose developed such a breadth and capacity that it started conveying every subject in common language. In the latter half of the 19th century, though the focus on prose literature waned, the light of the candle lit by the Fort William College spread from Bengal to the rest of the country. Under his influence, the Sir Syed movement gave more energy and scope to Urdu prose.